PENINGKATAN HASIL BELAJAR IPS MENGGUNAKAN MODEL KOOPERATIF TIPE THINK PAIR SHARE DI SEKOLAH DASAR - Farlita Elmahera; Sugiyono Sugiyono; Asmayani Salimi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractLack of teaching and learning interactions as well as the use of monotonous learning strategiescauses low student learning outcomes in social studies learning. This study aims to provideaccurate information regarding the use of Think Pair Share Type Cooperative models and seethe impact of improvement on student learning outcomes in VA class SDN 07 Pontianak Kota.The method used in this research is descriptive in the form of collaborative classroom actionresearch. The subjects were researchers and students of Class VA SDN 07 Pontianak Kotasemester 2 of 21 people. The implementation of this class action is carried out in 3 cycles. Theresults obtained are the ability of researchers in making plans to implement learning theaverage score of cycle 1 of 3.69. In cycle 2 it was 3.85 and in cycle 3 it was 3.93. The ability ofresearchers to carry out social studies learning process by using the Cooperative Think ThinkShare type model in cycle 1 was 3.66. in cycle 2 it was 3.78 and in cycle 3 it was 3.95. Studentlearning outcomes also increased in cycle 1 averaging 51.42, in cycle 2 averaging 55.23 and incycle 3 averaging 90.From the data collection, the research hypothesis is stated "If the teacheruses the Cooperative Learning model Think Pair Share type in social studies learning outcomeswill increase".Keywords: Cooperative Type Think Pair Share, and Learning Outcomes.